Penerapan Pendidikan Karakter dalam Pembentukan Akhlak Mulia di MTs Al-I’anah Karawang - Annisa Ghina Anggraeni; Masykur H Mansyur; Neng Ulya (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to examine and explain how the application of character education in the formation of noble character. This research was conducted at MTs Al-Ianah Karawang. The method used in this research is descriptive qualitative through observation, interview data collection, documentation, data reduction, data presentation, and drawing conclusions. The results of this study are character education has been applied in student learning, especially at MTs Al-Ianah Karawang. Character education in these schools is carried out in an integrated manner in all subjects, and habituation activities. Included in it is the process of socialization to all related elements to later carry out a good implementation, because there is still a moral decline in adolescents or students caused by several environmental factors and character education must run well in the cognitive, affective, and apsychomotor aspects in preparing the younger generation for the sustainability of the life of the people and the nation who have noble character and are better in the future.